Multi-scale integrated design and fabrication of ultra-broadband electromagnetic absorption utilizing multi-walled carbon nanotubes-based hierarchical metamaterial. (8th February 2023) - Zhou, Qian; Shi, Tiantian; Xue, Bei; Gu, Shengyue; Ren, Wei; Ye, Fang; Fan, Xiaomeng; Du, Lifei
Abstract: Ultra-broadband electromagnetic absorption has become a critical issue competing with advanced broadband electromagnetic detection systems. In this study, an innovative strategy for the broadband absorption is proposed via combining periodic patterns and the hierarchical structure with gradient electromagnetic performance, which introduces an abnormal electromagnetic response for improved maneuverability in impedance matching and multiple electromagnetic loss mechanisms. The electromagnetic parameters for each layer were determined by the fixing content of multi-walled carbon nanotubes (MWCNTs) in gypsum, and the periodic stepped meta-structure was optimized via the finite element simulation. The optimized hierarchical MWCNTs/gypsum metamaterial with a thickness of 8.0 mm realized an average absorption intensity of −21.6 dB (>99.3% absorption) in the frequency band of 4–40 GHz. Particularly, broadband EM absorption for reflection loss less than −10 dB and −15 dB was achieved in the ranges of 4.2–40 GHz and 5.6–40 GHz, respectively. The ultra-broadband and strong electromagnetic absorption properties of the proposed metamaterial should be the synergic result of the excellent impedance matching and the multiple EM wave loss caused by the multi-scale integrated structure. Therefore, the proposed MWCNTs/gypsum metamaterial with the innovative strategy of combining the hierarchical structure and periodic patterns, could provide an insight for achieving high-performance absorption materials. Graphical abstract: Image 1 Highlights: An innovative strategy combining periodic patterns and the hierarchical structure is proposed for broadband EM absorption. The effective absorption bandwidths for reflection loss less than −10 dB and −15 dB are 4.2–40 GHz, 5.6–40 GHz, respectively. The synergy of the impedance matching and the multiple electromagnetic wave loss is discussed with the multi-scale structure.